Program impact pathway analysis reveals implementation challenges that limited the incentive value of conditional cash transfers aimed at improving maternal and child health care use in Mali - Le Port, Agnès; Zongrone, Amanda; Sessou, Eric; Diatta, Ampa Dogui; Koulidiati, Jean-Louis; Ruel, Marie T. (Elsevier, 2019)
The program “Santé Nutritionnelle à Assise Communautaire à Kayes” (SNACK) in Mali aimed to improve child linear growth through a set of interventions targeted to mothers and children during pregnancy and up to the child's second birthday. Distributions of cash to mothers and/or lipid-based nutrient supplement (LNS) to children 6–23 months of age were added to SNACK to increase attendance at community health centers (CHCs).